Stewart Headlam's Radical Anglicanism : The Mass, the Masses, and the Music Hall - Orens, John (Book collections on Project MUSE., 2003)
Standing in stark contrast to the conservative churchmen of Victorian Britain, the Anglican clergyman Stewart Headlam was a passionately progressive reformer, a champion of the working poor - -especially women -- a defender of the music hall performers his colleagues attacked as licentious, and, in short, a man of God who remained firmly and controversially engaged with the society in which he lived and worked. With this intellectual biography, the first significant study of Headlam since 1928, Orens places Headlams life, beliefs, and actions in the context of the period, contributing to the ongoing debate about the proper relationship between Christianity, on the one hand, and society, sexuality, and the arts, on the other.